Failures of the legal imagination - Watson, Alan (University of Pennsylvania Press, 1988)
In this masterful choreography of legal philosophy, legal history, and comparative law, Alan Watson draws from ancient Roman, English, and French law to assess how lawmakers fail to envision ways to provide society with laws geared toward precise political or social goals.